Expectancy Outcomes and Self-Reported Alcohol Involvement in Educated Albanian Young Adults - Melonashi, Erika; Zahaj, Skerdi; Hysi, Greta; Peshkopia, Ridvan (Richtmann Publishing, 2012)
The World Health Organization (2004) has estimated that two billion people worldwide are alcohol consumers. Datafrom Albania indicate that at least 20% of Albanian adults fall into this category and an additional 1.5% of young people arealcohol dependent. Research has shown that people’s beliefs and expectations about the effects of alcohol play a role indrinking behavior. We assessed the role of expectancies on the effects of alcohol as predictors of self-reported involvement indrinking behavior. It was expected that both positive and negative expectancies would predict alcohol involvement, over andabove demographic variables. For the purpose of the study we recruited a non-probabilistic stratified sample of 450 Albanianstudents from three Albanian universities. The measures used were Leigh and Stacy’s Alcohol Outcome Expectancies Scale andMac Neill’s Index of Alcohol Involvement. Regression analyses separately conducted for those classifying themselves asdrinkers vs. nondrinkers. Thus, demographic variables were introduced in the first step, positive expectancies in the second stepand negative expectancies in the third. Results suggested that positive expectancies related to entertainment or sexual behaviorwere significantly explaining alcohol involvement among the drinkers group. On the other hand, only gender was significantlyexplaining drinking behavior among the non-drinkers group. Implications for practice were discussed.